2014
DOI: 10.1149/2.051403jes
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Particle Growth and Electrochemical Surface Area Loss due to Platinum Dissolution

Abstract: A model for coalescence/sintering of Pt nanoparticles is developed to analyze particle growth and electrochemical surface area (ECSA) loss measured in aqueous tests and in catalyst-coated membrane and gas diffusion electrode-containing single fuel cells. The model combines a non-ideal solid solution theory for Pt dissolution with the dynamics of particle size evolution considering particle growth by Ostwald ripening and coalescence/sintering. Results from the model indicate that the observed growth in particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
102
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 31 publications
7
102
0
Order By: Relevance
“…An enthalpy of dissolution of 49.3 kJ.mol −1 and an effective heat of fusion of 28.2 kJ.mol −1 for particle coalescence/sintering have been empirically determined from the measured temperature dependence of particle growth. 446 A systematic study is still needed to investigate the effect of O 2 on the thermodynamics and kinetics of Pt dissolution in aqueous media. Additionally, the model suggests that a reduction in ionomer hydration limits the diffusion of Pt ions in the ionomer; data is needed to estimate the platinum dissolution rate dependence on ionomer hydration.…”
Section: 142mentioning
confidence: 99%
“…An enthalpy of dissolution of 49.3 kJ.mol −1 and an effective heat of fusion of 28.2 kJ.mol −1 for particle coalescence/sintering have been empirically determined from the measured temperature dependence of particle growth. 446 A systematic study is still needed to investigate the effect of O 2 on the thermodynamics and kinetics of Pt dissolution in aqueous media. Additionally, the model suggests that a reduction in ionomer hydration limits the diffusion of Pt ions in the ionomer; data is needed to estimate the platinum dissolution rate dependence on ionomer hydration.…”
Section: 142mentioning
confidence: 99%
“…40,41,48,49 It has been speculated that this accelerated ECA loss is predominantly due to Pt dissolution and that the potentialdependent loss processes are linked to the relationship between dissolution and formation and reduction of platinum oxides. 46,50,51 However, there is disagreement as to the role of Pt oxides in Pt loss. Some authors speculate that Pt dissolution primarily occurs during the positive-going potential scan/step and is assisted by the formation of oxide, either directly or as a result of surface roughening incurred during oxide reduction 20,[52][53][54] or to chemical dissolution of Pt oxides.…”
mentioning
confidence: 99%
“…Cherevko et al 3 and Ahluwalia et al 4 demonstrated that Pt is also unstable during normal fuel cell operational potentials (≤1.0 V), i.e. when the formation of Pt oxide (and it's reduction) is somewhat negligible.…”
mentioning
confidence: 99%